2008
DOI: 10.1111/j.1439-0426.2008.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of a 50-mm diamond mesh knotless polyethylene codend for commercially important fish species in the Aegean Sea

Abstract: This research investigated effects of changing the diamond mesh size on codend selectivity in Mediterranean fisheries. The selectivity of a typical 50-mm diamond knotless polyethylene (PE) codend used in the Turkish fishery in the Aegean Sea was measured for commercially important species, in particular hake (Merluccius merluccius), horse mackerel (Trachurus trachurus), anglerfish (Lophius piscatorius) and John Dory (Zeus faber). Fishing trials were carried out on the commercial trawler ÔHapulog˘luÕ between 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
5
13
2
Order By: Relevance
“…An increase in mesh size from 48 mm to 56 mm could be made fruitless by an increase in codend circumference of only 13-17%. In agreement with Galbraith et al (1994) and Tosunoglu et al (2008) we have found that selectivity increases with larger mesh size but also decreases with wider codends. In the Mediterranean Sea, the effect of circumference might be not evident because the scarce catch size does not allow the meshes of the codend to stay open (Sala and Lucchetti, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…An increase in mesh size from 48 mm to 56 mm could be made fruitless by an increase in codend circumference of only 13-17%. In agreement with Galbraith et al (1994) and Tosunoglu et al (2008) we have found that selectivity increases with larger mesh size but also decreases with wider codends. In the Mediterranean Sea, the effect of circumference might be not evident because the scarce catch size does not allow the meshes of the codend to stay open (Sala and Lucchetti, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that there was an insufficient sieving effect of the mesh on jack mackerel with girths that were small enough to pass through the mesh in this study. Previous studies [33][34][35][36][37][38][39] have reported that the selection factor of diamond mesh codend for Trachurus fish varies from 2.0 to 3.43, and that of square mesh codend varies from 3.4 to 4.3, based on the measurement of the total length of the fish ( Table 4). The l 50 in fork length for the jack mackerel Trachurus japonicus estimated in this study corresponded to the l 50 in total length of 12.95 cm with the regression equation in Eq.…”
Section: Discussionmentioning
confidence: 98%
“…No anglerfish specimens were caught in Lb of either grid, mostly because of the body shape of the species. Tosunoğlu et al. (2008b) reported that due to the body shape (head and body depressed) no individuals could escape and that all (from 9 to 57 cm total length) were retained in the 50 mm diamond mesh codend.…”
Section: Discussionmentioning
confidence: 99%